2010
DOI: 10.1016/j.neuron.2010.06.030
|View full text |Cite
|
Sign up to set email alerts
|

When Giving Is Good: Ventromedial Prefrontal Cortex Activation for Others' Intentions

Abstract: Summary In social decision-making, people care both about others’ outcomes and their intentions to help or harm. How the brain integrates representations of others’ intentions with their outcomes, however, is unknown. In this study, participants inferred others’ decisions in an economic game during functional magnetic resonance imaging. When the game was described in terms of donations, ventromedial prefrontal cortex (VMPFC) activation increased for inferring generous play and decreased for inferring selfish p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(49 citation statements)
references
References 54 publications
2
47
0
Order By: Relevance
“…Positive correlation between activity and the values of chosen options and negative correlations with values of rejected options suggests a role in decision making (21) or attentional selection (23). However, there is also evidence the vmPFC tracks values of items even in the absence of any decision or when watching somebody else choosing (24,25). Some studies have suggested that these value representations are independent of reward type (money, food) (26) and reflect the impact of other Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Positive correlation between activity and the values of chosen options and negative correlations with values of rejected options suggests a role in decision making (21) or attentional selection (23). However, there is also evidence the vmPFC tracks values of items even in the absence of any decision or when watching somebody else choosing (24,25). Some studies have suggested that these value representations are independent of reward type (money, food) (26) and reflect the impact of other Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Three recent studies suggested that such vicarious decisions may involve neural valuation processes that are similar to those involved in choices that have consequences for oneself [68][69][70] . In one of these studies, BOLD activity in the vmPFC related to the participant's estimates of how much a pictured other person would contribute to a public good 68 . No vmPFC activation was observed if the participant estimated how much the depicted person would invest in a personal saving context.…”
Section: Vicarious Decision Makingmentioning
confidence: 99%
“…The anterior portion of the rostral medial PFC is activated in tasks that require subjects to make social judgments (Amodio and Frith, 2006). In particular, it may be important for adjusting initial impressions of individuals (Cooper et al, 2010; Croft et al, 2010) or comparing oneself to others (Ochsner et al, 2005; Tamir and Mitchell, 2010). The medial aspect of BA 10 is often activated in these tasks.…”
Section: Lesions To Medial Pfcmentioning
confidence: 99%